Directing Multicellular Organization by Varying the Aspect Ratio of Soft Hydrogel Microwells (Adv. Sci. 17/2022). Issue 17 (13th June 2022) - Pahapale, Gayatri J.; Tao, Jiaxiang; Nikolic, Milos; Gao, Sammy; Scarcelli, Giuliano; Sun, Sean X.; Romer, Lewis H.; Gracias, David H.
Abstract : Directing Multicellular Organization In article number 2104649, Lewis H. Romer, David H. Gracias, and co‐workers report the discovery of an endothelial cell self‐organization mechanism that is guided simply by tuning the aspect ratio of 3D geometry on soft hydrogel substrates. This mechanism is driven by a balance between intra‐ and extracellular interactions and is independent of protein or chemical patterning.